Recovery environments in places of daily living: a scoping review and conceptual analysis - Yumi Mizuochi; Yukako Shigematsu; Yoshitomo Fukuura (BMC Public Health)
Abstract Background Owing to advances in medical technology and the promotion of at-home medical care, patients are more frequently being treated in their places of daily living after discharge from acute care hospitals. As medical care and lifestyle are closely linked, the quality of life of the patient and their families therefore depends on the adequate preparation of the recovery environment. Hence, modifying this environment to ensure that the patient’s lifestyle and medical care are complementary is often vital. This study aimed to clarify the concept of recovery environments in places of daily living. Methods The literature search and selection of articles were based on a scoping review conducted in Scopus and PubMed, while data extraction and analysis were based on conceptual analysis. Thirty-two articles met the inclusion criteria. Results Our analysis of these articles allowed us to classify four types of recovery environments in places of daily living: physical environments appropriate to the health status of the recovering patient, collaborative environments in which intra-family roles are empowered, community environments in which recovering patients are accepted, and service environments in which the required services can be accessed. We also noted the main roles of medical professionals for building relationships with patients: providing decision-making support in places of daily living, creating an environment that empowers patients and their families, and modifying the service environment. Conclusions For patients, the main aims of recovery environments in places of daily living are to make them physically comfortable, maintain their identity, and improve their quality of life. Although this study is only a first step towards conceptualizing recovery environments in places of daily living and the final results are tentative, we are nonetheless confident that it will be important for advancing the field of home healthcare research.